Rekontruksi Kurikulum PAI Rahmatan Lil ‘Alamin Aman bagi Peserta Didik - Khoeron, Khoeron; Khozin, Khozin; Nurhakim, Moh (TSAQOFAH, 2024)
This article discusses efforts to reconstruct the Islamic Religious Education Curriculum. The concept of Rahmatan lil 'alamin is a step in reconstructing a curriculum whose content has the potential to lead to radicalism into a humanist curriculum to strengthen the spirit of tolerance (tasamuh) and moderation (tawasuth). This research method uses descriptive qualitative by obtaining data from scientific literature and campus media sources as research objects. The Rahmatan Lil'alamin Islamic Education Paradigm is a holistic and holistic way of thinking about the portrait of Islamic education which is built through universal values based on the Qur'an and al-Hadith, by prioritizing love (mahabbah) togetherness (ijtima'iyyah), justice ('is) and brotherhood towards others (ukhuwah). The results of this research explain that the Islamic religious education curriculum for the rahmatan lilalamin model includes all curriculum components, namely objectives, content, strategies or methods and evaluation. This model must foster a sense of tolerance, caring, justice, compassion, and be able to develop the interests and talents of the people around them.